Compensation, Organizational Culture, Education/Training of Work Motivation And Impact on The Performance Employees (Case Study : Hotel Sofyan Betawi, Jakarta) - Widiargo, Ruhadi; Walujadi, Dedi; Pasaribu, Popy Novita (Jurnal Manajemen, 2018)
The purpose of this study was to analyze the effect of compensation, organizational culture, education/training on work motivation both individually and collectively together and to analyze the effect of compensation, motivation, education/training on performance either individually or jointly, as well as to analyze the effect of compensation, organizational culture, education/training on performance through motivation to work at Hotel Sofyan Betawi, Cut Meutia, Jakarta. The population consisted of all employees, as many as 80 people. Using census sampling techniques to the overall population of 80 people or respondents, data collection was conducted using questionnaires, while data analysis using path analysis or path analysis were processed using SPSS 16 software. The results showed that: (1) Compensation and organizational culture had no significant effect on work motivation, while education/training has significant effect on work motivation, (2) Compensation, organizational culture, education/training jointly significant effect on motivation, (3) Compensation does not significantly affect the performance of the employee, while the motivation and education/training significantly affect performance, (4) compensation, motivation, education/training jointly significant effect on performance, (5) Compensation, organizational culture, education/training has positive influence on performance through motivation.